Methodology for determining bottlenecks on the city's street-road network by analyzing GPS track data - Riabushenko, Oleksandr; Рябушенко, Олександр Васильович (Харківський національний автомобільно-дорожній університет, 2023)
Problem. The article considers the issue of determining the location of "bottlenecks" on the highways of large cities based on the study of the vehicle's driving mode, obtained as a result of GPS data processing and analysis. Purpose. The purpose of this study is to develop and test the methodology for identifying potential "bottlenecks" on the city's freeway by analyzing the GPS track data of the car. The subject of the study is the interrelationship of the characteristics of the sections of the city’s street road network (SRN) with the parameters characterizing the vehicle movement mode in the traffic flow. Methodology. Two experimental routes with the same starting and ending points were chosen to obtain data on traffic conditions on the SRN of the city of Kharkiv, which correspond to typical routes of official movement of personal transport on weekdays. During the movement of the car along the specified routes, GPS tracks were obtained, whose processing made it possible to determine the driving condi tions along the entire length of the routes. Results. The work presents a method of researching the vehicle's driving mode by analyzing GPS track data; the determined indicators of the traffic regime, which can be effectively used as criteria for determining potential "bottlenecks" on the city's SRN; the methodology was tested on real traffic routes on the SRN of the city of Kharkiv. For selected routes, the work presents histograms of instantaneous speed distribution, graphs of car movement in "distance - speed" and "time - speed" coordinates. Graphs of changes in specific time in motion, specific idle time, speed gradient, energy gradient, Hermann-Prygozhin criterion were obtained for individual kilometer segments of routes. The specific idle time and the Herman-Prygozhin criterion turned out to be the most effective criteria for the purposes of determining the "bottlenecks" of SRN. Originality. An experimental technique was developed and tested, which allows to determine the potential "bottlenecks" of the city's SRN as a result of conducting short-term and not labor-intensive research. The proposed approach does not require the presence of specialized equipment or software, which makes this method effective when conducting scientific research. Practical value. The possibility of using the proposed method of data processing of GPS tracks to analyze traffic conditions on the city highway and identify potential "bot tlenecks" was shown. For the selected routes in Kharkiv, such sections turned out to be Vesnina St. (beyond the intersection with Pushkinska St.); Heroes of Stalingrad Ave. (access to the intersection from Leva Landau Ave.); Gagarina Ave. (access to the intersection with Kashtanova St.)
Методика визначення вузьких місць на вулично-дорожній мережі міста шляхом аналізу даних GPS-треків
Keywords: traffic; street-road network; GPS track; bottlenecks; traffic conditions; дорожній рух; вулично-дорожня мережа; GPS-треку; вузькі місця; умови руху.; 656.1/.5; 10.30977/AT.2219-8342.2023.52.0.08